2000
DOI: 10.1021/ic000217u
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinium and Imidazolium Borates Containing the First Examples of an Isolated Nonaborate Oxoanion:  [B9O12(OH)6]3-

Abstract: Borate compounds in which boron is bound only to oxygen have considerable mineralogical and industrial importance. These contain anionic components composed of BO 3 and BO 4 groups that may link together by sharing oxygen atoms to form isolated rings and cages or polymerize into infinite chains, sheets, and networks. Many examples of isolated boron oxoanions containing one to six borons exist in mineral and synthetic borates. However, isolated boron oxoanions having more than six borons are rare and no previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 3 publications
5
69
0
Order By: Relevance
“…DSC traces indicated that the decomposition steps below 250 o C were endothermic and those above 250 o C were exothermic. This is consistent with previous observations [15,26,27], which have shown the thermal decomposition generally occur via a series of steps involving dehydration (endothermic) and oxidation (exothermic), as shown in Eqns 3 and 4.…”
Section: Thermal Propertiessupporting
confidence: 93%
See 4 more Smart Citations
“…DSC traces indicated that the decomposition steps below 250 o C were endothermic and those above 250 o C were exothermic. This is consistent with previous observations [15,26,27], which have shown the thermal decomposition generally occur via a series of steps involving dehydration (endothermic) and oxidation (exothermic), as shown in Eqns 3 and 4.…”
Section: Thermal Propertiessupporting
confidence: 93%
“…Characterization data reported for 1 and 2 are limited to single-crystal XRD studies and elemental analyses [15,16]. We successfully re-synthesised these two compounds by the literature method [15], with bulk samples of satisfactory elemental analysis data.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations